2013
DOI: 10.1007/s00406-013-0411-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of autonomic nervous system by salivary alpha-amylase level and heart rate variability in patients with schizophrenia

Abstract: Several researches indicate that autonomic nervous system (ANS) dysfunction in patients with schizophrenia. Recently, salivary alpha-amylase (sAA) has been employed as a useful marker for ANS function. We investigated the extent of ANS dysfunction by measuring sAA and heart rate variability (HRV) of 25 patients with schizophrenia compared with controls. Schizophrenia group demonstrated a significant increase in sAA and markedly lower parasympathetic nervous system (PNS) activity in the HRV. However, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 40 publications
3
39
1
Order By: Relevance
“…Present findings limited to the assessment of salivary α-amylase to the time immediately after awakening and showing no drop of the enzyme after awakening in schizophrenic patients suggest enhanced activity of the sympathetic branch of the ANS in chronic schizophrenia. Consistent with our data, a Japanese research group recently reported increased levels of salivary α-amylase at one single time point in the morning in a sample of clinically stabilized chronic schizophrenic patients treated with both first- and second-generation antipsychotic drugs [36,37]. …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Present findings limited to the assessment of salivary α-amylase to the time immediately after awakening and showing no drop of the enzyme after awakening in schizophrenic patients suggest enhanced activity of the sympathetic branch of the ANS in chronic schizophrenia. Consistent with our data, a Japanese research group recently reported increased levels of salivary α-amylase at one single time point in the morning in a sample of clinically stabilized chronic schizophrenic patients treated with both first- and second-generation antipsychotic drugs [36,37]. …”
Section: Discussionsupporting
confidence: 79%
“…Finally, it has been questioned whether chewing on the Salivette swabs would result in reliable salivary α-amylase levels [42]; hence, measuring the salivary flow rate in our participants would have helped to overcome these issues. Although we cannot exclude that our results were affected by psychotropic drug treatment, our study is comparable to other published studies that included antipsychotic-treated patients compared to nontreated healthy controls [26,27,28,29,36,37]. …”
Section: Discussionsupporting
confidence: 76%
“…The physiological mechanism by which anxiety affects autonomic nervous function, and especially sAA levels, remains unclear. Ieda et al [19] detected a significant increase in sAA levels in schizophrenia patients and speculated that the PNS was suppressed, whereas the SNS exhibited relatively high activity (according to HRV measurement). sAA has been suggested to be a surrogate for cardiovascular autonomic system balance correlating well with HRV parameters [27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a total of one minute was required for measuring sAA activity. We previously used this methodology to analyze sAA in other studies [14] [18] [19]. To control for circadian variations in sAA, one-time saliva was conducted in the morning (10:00 -12:00 AM).…”
Section: Measurement Of Salivary Alpha-amylasementioning
confidence: 99%
“…Albeit the authors found evidence that the CLOCK gene's association with clinical ADHD samples may be generalizable to traits measured in the general population, a mediating role of evening preference, however, could not be verified. Based on findings of a dysfunction of the autonomic nervous system (ANS) in schizophrenia patients, Ieda et al [7] used the marker salivary alpha-amylase (sAA) for ANS function to investigate this dysfunction by measuring sAA and heart rate variability of 25 schizophrenic patients compared with controls. The authors found a significant increase in sAA plus considerably lower parasympathetic nervous system activity in the heart rate variability in the patient sample but no significant group differences in sympathetic nervous system activity.…”
mentioning
confidence: 99%